The Political and Commercial Dynamics of Russia’s Gas Export Strategy - Henderson, J; Mitrova, T (Oxford Energy Institute, 2015)
Gas exports have historically provided a foundation of economic and political strength for Russia and a source of significant revenues for its leading gas company, Gazprom. However, lower commodity prices, the imposition of sanctions on Russia in light of the Ukraine crisis, lower gas demand in Europe, the EU’s desire to diversify away from Russian gas and increasing competition from new global LNG supply are presenting multiple challenges. A search for new markets in Asia, and especially China, has begun, but is currently not progressing as fast as Russia would have hoped, while domestically Gazprom’s position is being challenged by third parties who are keen to break the company’s export monopoly. This paper, jointly authored by James Henderson and Tatiana Mitrova, examines the emerging trends in Russia’s export strategy, identifying the key political drivers as well as the commercial factors that are influencing policy making. It analyses the catalysts behind Russia’s “pivot to Asia” in the gas sector, assesses the likelihood of this strategy being a success and argues that Europe will remain of vital importance as a major market for Russian gas for the foreseeable future. In light of this, the paper also examines Gazprom’s evolving gas marketing strategy and asks whether the company is adapting to the changes in European regulation and legislation in a positive manner. It considers the competitive position of Russian gas in Europe and Asia, delivered both by pipeline and by potential new LNG projects, and argues that Russian gas can have a pivotal role in both markets as its cost of supply is relatively low. Indeed, although it would currently appear that Gazprom’s strategy is being somewhat improvised in reaction to political and commercial events, the authors’ conclude that the company is gradually edging towards a more market-based outlook that could ultimately allow it to prosper even in a more competitive global gas market. It will need to continue this trend if it is to fend off competition from expanding global LNG supply but also from domestic competitors such as Novatek and Rosneft, who are keen to provide their own solutions to the challenges facing Russia’s gas export business.